Dobry czy piękny? Zły czy brzydki? Moralno-estetyczne rozterki polsko-włoskie = Good or beautiful? Bad or ugly? Polish-Italian moral-aesthetic dilemmas - Piekarz, Danuta (Zielona Góra: Uniwersytet Zielonogórski, Instytut Filologii Polskiej)
Probably in all languages, the basic criteria for assessing people, things or phenomena are aesthetic (nice/ugly) and moral (good/bad) criteria. However, the terms belonging to these two categories alternate, expressing more generally positive or negative assessments. No wonder certain phenomena described as "pretty" in some languages will be considered "good" in others or expressed in terms of other adjectives - and vice versa. The same is true for negative evaluations.
Keywords: gramatyka kontrastywna; język polski; język włoski; dobry/zły; ładny/brzydki; contrastive grammar; Polish; Italian; good/bad; nice/ugly